Pemahaman Konsep dan Penalaran Matematika Siswa dalam Pembelajaran Matriks - Munasiah Munasiah; Ai Solihah; Heriyati Heriyati (SAP (Susunan Artikel Pendidikan), 2020)
The purpose of this study is to determine the relationship and influence of understanding mathematical concepts with mathematical reasoning in learning matrix on grade XI of senior high school. In this study the survey method was conducted using random sampling. The scores were obtained from the 54 students' understanding and mathematical reasoning tests. Based on SPSS calculations 20. Correlation coefficient between the understanding of mathematical concepts with mathematical reasoning is 0.695, meaning a strong relationship. The significance value is 0,000 <0,005 which means that it is significant. The regression equation is  = -0,989 + 9,71, if there is no concept understanding then mathematical reasoning is negative. The regression coefficient X value of 9.71 states that each addition of one value to the understanding of mathematical concepts will increase mathematical reasoning by 9.71. From the data and analysis above, it is shown that there is a significant relationship between understanding concepts and students' mathematical reasoning on the matrix material, indicated by the correlation coefficient of 0.695, which means a strong relationship, sig. 0,000 <0.005 that means significant.